MEMBACA LUKISAN AGUS SUWAGE:`THE SUPER OMNIVORE` - Lilik Indrawati (Fakultas Sastra Universitas Negeri Malang, 2012)
Appreciating the Indonesian contemporary work of painting created by Agus Suwage must be related to the painter’s birth, existence, culture, and the nation environments condition. Mostly, Suwage exploit himself as an object which later on becomes a medium to express his restlessness through his ideas . The object of self portrait in Suwage’s painting is a metaphoric icon. However, the portraiture technique which is chosen by Suwage in his paintings does not tell a story about himself.